The antivirulence activity, transcriptomics of EGCG and its protective effects on zebrafish infected by Aeromonas hydrophila - Yin, Hongmei; Yan, Qiaohua; Cheng, Guoqiang; Zhang, Li; Li, Meiqing; Hu, Tingting; Gao, Sihui; Chen, Yuanhang; Tang, Huaqiao; Luo, Jie (Frontiers in Cellular and Infection Microbiology, 2023)
Background Aeromonas hydrophila is an important pathogen that mainly harms aquatic animals and exhibits resistance to a variety of antibiotics. This study investigated the effect of epigallocatechin-3-gallate (EGCG) on the virulence factors of A.hydrophila and its impact on adhesion, invasion, and cytotoxicity in Caco-2 cells. The potential mechanism of antibacterial activity of EGCG was investigated by transcriptomic analysis. Results EGCG not only inhibited the production of biofilm, hemolytic activity, motility, and protease activity of A.hydrophila, but also reduced its adhesion, invasion, and cytotoxicity in Caco-2 cells. Transcriptomic analysis indicated that the antimicrobial activity of EGCG may be achieved by weakening the chemotaxis and stress response of the bacteria, as well as inhibiting the TonB system. Animal studies demonstrated that EGCG can significantly improve the survival rate and organs damage of zebrafish infected with A.hydrophila. Conclusion EGCG would be a potential alternative drug for the prevention and treatment of A. hydrophila infections by anti-virulence mechanism.